The Physiological Benefits and Economic Value of Using Fairy Shrimp as Fish Meal for Flowerhorn Cichlids; Amphilophus citrinellus (Günther, 1864) × Cichlasoma trimaculatum (Günther, 1867) - Ploychompoo Weber; Supranee Wigraiboon; Nantaporn Sutthi; Pattira Kasamesiri; Wipavee Thaimuangphol (Fishes)
The aim of this study was to evaluate the utilization of fairy shrimp (Branchinella thailandensis) meal in the diets of flowerhorn cichlids, on their growth, skin coloration, carotenoid content, antioxidant activity, and innate immunity. The fish were fed diets incorporated with fairy shrimp meal at 0% (control; FS0), 10% (FS10), 20% (FS20), and 30% (FS30) for 60 days. The results showed that growth performance and chemical composition were not significantly different among treatments (p > 0.05), whereas fish fed the 30% fairy shrimp meal (FS30) diet represented significantly enhanced skin coloration, particularly in terms of redness (a*) and dominant wavelength (H°ab). The highest level of antioxidant enzymes and non-specific immune enzymes such as SOD and lysozyme were observed in the fish fed the FS30 diet. Meanwhile, increasing fairy shrimp meal significantly reduced the liver function markers (ALT and AST), and decreased lipid peroxidation. These findings suggest that fairy shrimp meal serves as a valuable dietary ingredient for enhancing skin pigmentation, boosting antioxidant defense, and stimulating immune responses in flowerhorn cichlids. Moreover, the economic evaluation of using fairy shrimp meal as an ingredient for ornamental fish demonstrates promising investment potential, supporting its application in commercial aquaculture.